Prevalence and impact of bladder and bowel disorders in women with breast cancer: A systematic review with meta‐analysis. Issue 1 (5th October 2020) - Colombage, Udari N.; Lin, Kuan‐Yin; Soh, Sze‐Ee; Frawley, Helena C.
Abstract: Background: One of the consequences of breast cancer treatments may be the onset of new, or aggravation of preexisting bladder and bowel disorders. However, the presence and impact of these disorders in women with breast cancer are poorly documented. The aim of this systematic review was to assess the prevalence, incidence and impact of bladder and bowel disorders in women undergoing breast cancer treatment. Methods: A systematic search of six databases was conducted. Pooled prevalence rates and impact of bladder and bowel disorders were calculated using random‐effects models. Results: A total of 32 studies met the inclusion criteria, and 17 studies were included in the meta‐analyses. The pooled estimate of women who experienced bladder disorders following sensitivity analysis, which removed one study reporting a result that deviated from the pooled estimate, was 38% (95% confidence interval [CI]: 32%–44%; I 2  = 98%; n  = 4584). The impact of bladder and bowel disorders on women's daily lives was relatively low (bladder [scale: 0–4]: mean: 0.8; 95% CI: 0.4–1.1; I 2  = 99%; n  = 4908; bowel [scale: 0–100]: mean 14.2; 95% CI: 9.4–19; I 2  = 95%; n  = 1024). Conclusion: This is the first study to comprehensively document the magnitude of bladder and bowel disorders in the breast cancer population. This meta‐analysis found that women with breast cancer had a higher prevalence of urinary incontinence (38%) compared to women without breast cancer (21%). Given the extent and impact of our findings, screening and management of bladder and bowel disorders may be indicated in women with breast cancer to improve their health‐related quality of life.